Recent Developments in the Canadian Economy: Fall 2023 - Guy Gellatly; Carter McCormack (Economic and Social Reports)
This article provides an integrated summary of recent changes in output, consumer prices, employment and household finances. It highlights changes in the economic data during the first half of 2023 and into the summer months. The article also examines how economic conditions have changed as borrowing costs have risen.